A Gut Symbiotic Bacterium Serratia marcescens Renders Mosquito Resistance to Plasmodium Infection Through Activation of Mosquito Immune Responses - Bai, Liang; Wang, Lili; Vega-Rodríguez, Joel; Wang, Guandong; Wang, Sibao (Frontiers in Microbiology, 2019)
The malaria development in the mosquito midgut is a complex process that results in considerable parasite losses. The mosquito gut microbiota influences the outcome of pathogen infection in mosquitoes, but the underlying mechanisms through which gut symbiotic bacteria affect vector competence remain elusive. Here, we identified two Serratia strains (Y1 and J1) isolated from field-caught female Anopheles sinensis from China and assessed their effect on Plasmodium development in An. stephensi. Colonization of An. stephensi midgut by Serratia Y1 significantly renders the mosquito resistant to Plasmodium berghei infection, while Serratia J1 has no impact on parasite development. Parasite inhibition by Serratia Y1 is induced by the activation of the mosquito immune system. Genome-wide transcriptomic analysis by RNA-seq shows a similar pattern of midgut gene expression in response to Serratia Y1 and J1 in sugar-fed mosquitoes. However, 24 h after blood ingestion, Serratia Y1 modulates more midgut genes than Serratia J1 including the c-type lectins (CTLs), CLIP serine proteases and other immune effectors. Furthermore, silencing of several Serratia Y1-induced anti-Plasmodium factors like the thioester-containing protein 1 (TEP1), fibrinogen immunolectin 9 (FBN9) or leucine-rich repeat protein LRRD7 can rescue parasite oocyst development in the presence of Serratia Y1, suggesting that these factors modulate the Serratia Y1-mediated anti-Plasmodium effect. This study enhances our understanding of how gut bacteria influence mosquito-Plasmodium interactions.